2021
DOI: 10.29271/jcpsp.2021.11.1375
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of OPRM1 A118G Polymorphism on the Dosage of Morphine in Patients with Advanced Liver Cancer

Abstract: This study was conducted to investigate the influence of μ-opioid receptor gene (OPRM1) A118G polymorphism on dosage of morphine in advanced liver cancer patients. Seventy patients with advanced liver cancer at Changyi People's Hospital, Shandong Province, China, were included from February 2019 to December 2020. The dosage of morphine in patients with OPRM1 A118G different genotypes was compared. Thirty patients (42.86%) were of AA genotype, 35 (50.00%) were AG genotype and 5 (7.14%) were GG genotype. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Additionally, the analgesic effects of morphine and fentanyl are mediated by the µ-opioid receptor. There is evidence that the G allele found in our patient is associated with increased morphine or fentanyl consumption [ 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussion and Pharmaceutical Assessmentmentioning
confidence: 82%
“…Additionally, the analgesic effects of morphine and fentanyl are mediated by the µ-opioid receptor. There is evidence that the G allele found in our patient is associated with increased morphine or fentanyl consumption [ 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussion and Pharmaceutical Assessmentmentioning
confidence: 82%
“…OPRM1 A118G mutation is the most common and reported functional gene. Some studies have shown that its gene mutation reduces the efficacy of various opioids, and patients with GG need more opioids to relieve pain [ 10 13 ].On the other hand, some studies have shown that OPRM1 A118G mutation can enhance the analgesic effect of patients [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%